2019
DOI: 10.1021/acs.macromol.9b01852
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Liquid Crystal Network Particles Synthesized via Precipitation Polymerization

Abstract: The production of liquid crystalline (LC) polymer particles with a narrow size distribution on a large scale remains a challenge. Here, we report the preparation of monodisperse, cross-linked liquid crystalline particles via precipitation polymerization. This versatile and scalable method yields polymer particles with a smectic liquid crystal order. Although the LC monomers are randomly dissolved in solution, the oligomers self-align and LC order is induced. For the polymerization, a smectic LC monomer mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Initial studies were conducted in phenyl acetate at 65 8 8Cb ased on our earlier results using as imilar LC monomer mixture containing ad ifferent cross-linker,v ide supra. [45] Ther esulting polymer particles were flower-like,w ith "petal" moieties on the surfaces (Figure 1b and c). Thea verage diameter of the particles was % 750 nm, with acoefficient of variation (CV) of 7.2 %and an average circularity of 0.59.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies were conducted in phenyl acetate at 65 8 8Cb ased on our earlier results using as imilar LC monomer mixture containing ad ifferent cross-linker,v ide supra. [45] Ther esulting polymer particles were flower-like,w ith "petal" moieties on the surfaces (Figure 1b and c). Thea verage diameter of the particles was % 750 nm, with acoefficient of variation (CV) of 7.2 %and an average circularity of 0.59.…”
Section: Resultsmentioning
confidence: 99%
“…Since previous publications indicated that the polymerization conditions,i ncluding the solvent and polymerization temperature,m ay have profound influence on particle morphologies,L Cp olymer particles were prepared using aseries of solvent mixtures and polymerization temperatures to reveal the impact of these conditions. [45,47]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 57 , 58 , 59 , 60 ] LC polymer particles have been successfully prepared by precipitation polymerization of an LC monomer mixture consisting of benzoic‐acid functionalized acrylates and LC diacrylates (Figure 12 a). [61] The particle diameters were between 0.6 and 1.4 μm, mainly affected by the solvent and polymerization temperature. The polydispersity is lower than the similar particles preapred by suspension polymerization (Figure 6 ).…”
Section: Dispersion and Precipitation Polymerizationmentioning
confidence: 99%
“… [28] However, the control of alignment and preparation of non‐radial LC polymer particles by precipitation polymerization have not yet been reported. [61] …”
Section: Dispersion and Precipitation Polymerizationmentioning
confidence: 99%